Green Synthesis and the Study of Some Physical Properties of MgO Nanoparticles and Their Antibacterial Activity - Ali, Rand; Shanan, Zainab J.; Saleh, Ghada Muhammad; Abass, Quraysh (Iraqi Journal of Science, 2020)
Magnesium oxide nanoparticles (MgO NPs) were synthesized by a green method using the peels of Persimmon extract as the reducing agent , magnesium nitrate, and NaOH. This method is eco-friendly and non-toxic. In this study, an ultrasound device was used to reduce the particle size, with the impact on the energy gap was set at the beginning at 5.39 eV and then turned to 4.10 eV. The morphological analysis using atomic force microscopy (AFM) showed that the grain size for MgO NPs was 67.70 nm which became 42.33 nm after the use of the ultrasound. The shape of the particles was almost spherical and became cylindrical. In addition the Field-Emission Scanning Electron Microscopy (FESEM) analysis showed that the average particle size was reduced and the spherical shape was changed into cylindrical flakes. The antibacterial activity of MgO Nps was measured against both gram positive and negative bacteria (Staphylococcus aureus and Escherichia coli, respectively) for both the synthesized and the scaled-down particles by the ultrasonic. MgO NPs showed an efficacy at a minimum inhibitory concentration (MIC) of 500 Î¼g/ml, with the better effect being observed after the ultrasonic treatment of the MgO NPs.